No Boundaries Here: Brecht, Lauwers & European Theatre after Postmodernism - Freeman, John (Cambridge University Press, 2013)
In this article John Freeman focuses on theatre after postmodernism as exemplified by the Belgium-based Needcompany. If, as is suggested here, we are all more than a little ‘postmoderned out’ through an over-dependence on individualism, the shadow cast by postmodernism remains large in the contemporary Western world, and its impact is still clearly felt. As the postmodern came to offer a safety net through which bad practice could not easily fall, the modernist theatre it followed offered its own elusive ideal. In arguing this, Freeman forges links between Brecht's knowing embrace of amateurism and the faux uncertainty of much contemporary work, where Brecht the arch-dramatist becomes the archetype of the postdramatic, as twenty-first century theatre moves in the shadow of the past. John Freeman has written extensively on contemporary performance, creative learning, and arts policy. He is currently Associate Professor at Curtin University, Western Australia, where he leads the Humanities Honours programme.